Засоби автоматизації роботи архівних підрозділів організації - Білущак, Тетяна; Лужецька, Роксолана; Ольховик, Вероніка (Видавництво Львівської політехніки, 2016)
This article contains information about automation of archivist’s workplace, advantages of electronic archive and free software. Advantages of free programs are show on concrete examples, which are convenient and useful in use. The review of systems of electronic document circulation is also given in the article and these systems provide with archive service “LandDocs”, Megapolis.DocNet, ASKOD and other software. The article covers all problems and needs of archivist’sproductive work.
Keywords: electronic archive; electronic document circulation; the software; OpenOffice.org; the templates; the automated workplace of the archivist